Risperidone-Induced Erythema Multiforme Minor: A Case Report - Negintaji, Sina; Bidaki, Reza; Zare Kamali, Javad; Saghafi, Fatemeh; Naseri Bafrouie, Maryam; Tabaei Zadeh, Nilofar; Azadi, Hossein (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Erythema Multiforme (EM) is a hypersensitivity reaction that can be triggered by an infection or particular medications. Erythema multiforme minor (EM minor) represents localized skin lesions with minimal or no mucosal involvement. Only a few case of EM associated with risperidone are found in the scientific literature. In this case report, the administration of the risperidone resulted in the rapid appearance of skin lesions. Erythematous lesions were recovered upon discontinuation of the drug and no new skin lesion was observed. A 52-year-old male patient was admitted to the psychiatry hospital because of developing schizophrenic symptoms. At the time of admission, risperidone was added to her previous drug regimen. Two weeks later, the patient returned with a complaint of progressively increasing rashes over his body. The patient was diagnosed with EM minor. The prescribed risperidone was discontinued due to its side-effect profile and the patient’s drug regimen was changed entirely to the olanzapine, haloperidol, and topical clobetasol. At one month follow up visit, his skin lesions were satisfactorily controlled.